2022
DOI: 10.1371/journal.pone.0262955
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and preliminary efficacy for morning bright light therapy to improve sleep and plasma biomarkers in US Veterans with TBI. A prospective, open-label, single-arm trial

Abstract: Mild traumatic brain injury (TBI) is associated with persistent sleep-wake dysfunction, including insomnia and circadian rhythm disruption, which can exacerbate functional outcomes including mood, pain, and quality of life. Present therapies to treat sleep-wake disturbances in those with TBI (e.g., cognitive behavioral therapy for insomnia) are limited by marginal efficacy, poor patient acceptability, and/or high patient/provider burden. Thus, this study aimed to assess the feasibility and preliminary efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…Blue light, however, is not all “bad”. Exposure to bright light (bright light therapy; BLT) [ 256 , 257 , 258 ] early in the biological morning [ 259 ] can also help synchronize individuals’ rhythms in a variety of contexts [ 256 , 260 , 261 , 262 ]. Indeed, BLT has been used to treat the symptoms of seasonal affective disorder (SAD) when administered early in the biological day [ 256 , 257 ].…”
Section: Strategies To Remediate Effects On Disrupted Rhythms In Humansmentioning
confidence: 99%
“…Blue light, however, is not all “bad”. Exposure to bright light (bright light therapy; BLT) [ 256 , 257 , 258 ] early in the biological morning [ 259 ] can also help synchronize individuals’ rhythms in a variety of contexts [ 256 , 260 , 261 , 262 ]. Indeed, BLT has been used to treat the symptoms of seasonal affective disorder (SAD) when administered early in the biological day [ 256 , 257 ].…”
Section: Strategies To Remediate Effects On Disrupted Rhythms In Humansmentioning
confidence: 99%
“…The results on the effect of light therapy on inflammation are scarce. In a preliminary study, Elliott et al reported a significant decrease in IL-6 and TNF-α levels following light therapy in the morning in patients with traumatic brain injury [ 225 ]. In contrast, no effect on IL-6 levels was observed following light therapy in patients with seasonal affective disorder [ 226 ].…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…This treatment incorporates cognitive and behavior-change techniques and targets dysfunctional attitudes, beliefs, and habits involving sleep [ 102 ]. Bright-light therapy is also used to improve sleep, but to our knowledge not formally tested in advanced cancer patients [ 103 ]. Short-term pharmacological treatment may be necessary until CBI-I takes effect or for those being refractory to CBT-I.…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 99%